2006
DOI: 10.1051/0004-6361:20054312
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the NIR-silhouette massive disk candidate in M 17

Abstract: Aims. The physical properties of the massive disk candidate in the star-forming region M 17 are analyzed. Methods. Making use of the rare configuration in which the gas and dust structure is seen in silhouette against the background radiation at λ = 2.2 µm, we determine the column density distribution from a high-resolution NAOS/CONICA image. The influence of scattered light on the mass determination is analyzed using 3D radiative transfer calculations. Further upper flux limits derived from observations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Previous observations of massive stars reported disk mass ranges of < ∼ 0.1 M to ∼1 M ; e.g. Ori IRc2; Plambeck et al (1995); Blake et al (1996), Cep A; Patel et al (2005), and M 17; Steinacker et al (2006). These results might have implications for the evolutionary stage of the system, although some of these differences could be due to the use of different methods to estimate the disk parameters (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous observations of massive stars reported disk mass ranges of < ∼ 0.1 M to ∼1 M ; e.g. Ori IRc2; Plambeck et al (1995); Blake et al (1996), Cep A; Patel et al (2005), and M 17; Steinacker et al (2006). These results might have implications for the evolutionary stage of the system, although some of these differences could be due to the use of different methods to estimate the disk parameters (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Preibisch et al 2003;Alvarez et al 2004;Weigelt et al 2006;Kraus et al 2006) and radio interferometry (e.g. Menten & van der Tak 2004;Patel et al 2005;Steinacker et al 2006). Furthermore, the circumstellar environment of young stellar objects (YSOs) is also known to be a molecule-forming region.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of circumstellar discs are based on detailed comparisons of high-quality data sets, combining various kinds of observation (SED, multiple wavelength scattered light images, polarisation map, infrared or millimetre visibilities) to the predictions of RT codes (e.g. Wood et al 2002;Watson & Stapelfeldt 2004;Wolf et al 2003;D'Alessio et al 2006;Steinacker et al 2006;Doucet et al 2007;Fitzgerald et al 2007;Pontoppidan et al 2007;Pinte et al 2007Pinte et al , 2008aGlauser et al 2008;Tannirkulam et al 2008). Such studies will become more and more common with the advent of new instruments like VLT/SPHERE, Gemini/GPI, JWST, Herschel and ALMA, and validating the accuracy of RT codes is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant observational evidence has been found that the accretion scenario is also valid in the regime of high-mass star formation (Beltrán et al 2006;Beuther et al 2006;Beuther & Steinacker 2007;Puga et al 2006;Keto & Wood 2006;Steinacker et al 2006). This poses the question of whether the initial conditions under which massive stars form are also comparable to low-mass star birth, i.e.…”
Section: Introductionmentioning
confidence: 99%